Primary Spinal Cord Melanoma of Intradural Extramedullary Origin - Sharma, Ashish (J Neurosci Rural Pract, 2019)
Primary malignant melanoma is the very rare entity of the central nervous system. It accounts only 1% of all melanoma cases. A 67-year-old patient presented to us with lower back pain radiating to the left lower limb and progressive weakness of both lower limbs. She underwent magnetic resonance imaging scan of lumbosacral region that suggested T1 hyperintense, T2 hypointense, extramedullary altered signal intensity lesion at L1 and L2 vertebral level compressing terminal spinal cord, and cauda equine region. On histopathological examination, findings were suggestive of malignant melanoma that was confirmed with immunohistochemistry examination (positive for S-100, Melan-A, and HMB-45). Here, we are discussing an unusual case of primary malignant melanoma of conus and cauda equine region with comprehensive review regarding management and prognosis of the tumor.